2015
DOI: 10.1093/toxsci/kfv208
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Low-Level Drug Effects Using Real-Time,in vitroMeasurement of Oxygen Consumption Rate

Abstract: There is a general need to detect toxic effects of drugs during preclinical screening. We propose that increased sensitivity of xenobiotics toxicity combined with improved in vitro physiological recapitulation will more accurately assess potentially toxic perturbations of cellular biochemistry that are near in vivo pharmacological exposure levels. Importantly, measurement of such cytopathologies avoids activating mechanisms mediating toxicity at suprapharmacologic levels not relevant to in vivo effects. We pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…Inhibition of the oxygen consumption rate (19,59) or glucose (pyruvate) oxidation by high metformin are consistent with inhibition of complex 1 and mimicked by rotenone. In this study we found inhibition of glucose oxidation by 0.5 mM but not by 0.2 mM metformin, and this concurs with studies showing inhibition of oxygen consumption at Ն 0.3 mM metformin (68). Although high metformin (Ն0.5 mM) promotes a more reduced mitochondrial NADH/NAD ratio, consistent with complex 1 inhibition (31), low metformin (Յ0.2 mM) promotes a more oxidized NADH/NAD ratio and increased ␤-octanoate oxidation, implicating increased electron transport (31).…”
Section: Metformin Lowers Glucose 6-phosphate In Hepatocytessupporting
confidence: 93%
“…Inhibition of the oxygen consumption rate (19,59) or glucose (pyruvate) oxidation by high metformin are consistent with inhibition of complex 1 and mimicked by rotenone. In this study we found inhibition of glucose oxidation by 0.5 mM but not by 0.2 mM metformin, and this concurs with studies showing inhibition of oxygen consumption at Ն 0.3 mM metformin (68). Although high metformin (Ն0.5 mM) promotes a more reduced mitochondrial NADH/NAD ratio, consistent with complex 1 inhibition (31), low metformin (Յ0.2 mM) promotes a more oxidized NADH/NAD ratio and increased ␤-octanoate oxidation, implicating increased electron transport (31).…”
Section: Metformin Lowers Glucose 6-phosphate In Hepatocytessupporting
confidence: 93%
“…OCR in the two channels that were not exposed to acetaminophen remained flat, whereas the OCR was lowered 40 and 60% by 6 and 15 mM acetaminophen. These results were similar to those obtained in a previous study with our larger peristaltic pump-driven perifusion system [10].…”
Section: Resultssupporting
confidence: 92%
“…Samples of the effluent perfusate can be collected for off-line assay—we routinely measure insulin release rate, or lactate production for example. We can also simultaneously measure the tissue’s OCR using opto-electronic sensing of the fluorescence decay rate of an oxygen-sensitive dye painted either on glass beads or on the inner column surface as routinely used in our prior studies [10]. Thus, the BaroFuse can combine conventional chemical and radioimmunological assays with OCR as a powerful index of cellular health and function.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The microfluidic flow conditions also allow for constant replenishment of oxygen and nutrients, and concomitant removal of cell products, thereby reducing potential detrimental effects of paracrine cues that can accumulate in static systems50.…”
Section: Discussionmentioning
confidence: 99%